Guarding the invisible dragons - West, Tracey, 1965- (West, Tracey, 1965- Dragon Masters, 2022)
A nest of invisible baby dragons has been discovered in Queen Sofia's castle so Drake, Worm, and Val, Carlos's cousin, must journey to the dangerous Dove Island to find the parents and the fruit that keeps the dragons' invisible powers.